Fresh and Early-Age Properties of Cement Pastes and Mortars Blended with Nickel Slag - Rahman, M.A.; Sarker, Prabir; Shaikh, Faiz (Concrete Institute of Australia, 2015)
Usage of industrial by-product materials in concrete is increasing because this is a sustainable way to manage the by-products and convert them into economic values. This paper presents the properties of fresh and hardened cement pastes and mortars blended with a proprietary nickel slag. Water demand slightly reduced with the increase of the slag content in determination of normal consistency. Incorporation of the slag with cement slightly prolonged initial and final setting time. The Le-Chatelier soundness test results did not show any increase in expansion for cement replacement of up to 65% by the slag though it has high magnesium content. The strength activity index of the slag was found to be 84% at 28 days when 20% of cement was replaced by the slag. Cement was replaced by the slag at rates of 20-50% in mortar mixtures having water to binder ratio of 0.5. Results show that 30% and 50% replacement of cement by the slag provided about 83% and 66% compressive strength respectively compared to that of 100% cement mortar specimens.